Starsight - Sanderson, Brandon (Sanderson, Brandon. Skyward, 2019)
"As if the threat of huge, raging monsters from hyperspace isn't scary enough, hotshot fighter pilot Spensa Nightshade becomes embroiled in an alien empire's politics"--